1997
DOI: 10.1111/j.1432-1033.1997.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐Cell Contact Activates the Long Terminal Repeat of Human Immunodeficiency Virus 1 Through its κB Motif

Abstract: Cell-to-cell contact between peripheral blood lymphocytes and transfected human colonic carcinoma cell line HT29 activates transcription of the long terminal repeats (LTR) of human immunodeficiency virus. HIV-1 LTR transcription is controlled by a complex array of virus-encoded and cellular proteins.Using various constructs expressing a 2acZ reporter gene under the control of the intact or three deleted forms of HIV-1 LTR, we obtained evidence that the KB regulatory elements located in the U3 region are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Our data indicate that even though some interactions by soluble factors (e.g., cytokines) can occur, close proximity or contact of cells is required for full induction. These results are consistent with other investigations demonstrating that conditioned medium from M and other cell types did not induce viral replication in U1 and ACH2 cells to the same magnitude as that obtained by cell-cell contact (20,27). The inductive effect required the presence of viable M , since we found that paraformaldehyde-fixed M did not induce viral replication.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data indicate that even though some interactions by soluble factors (e.g., cytokines) can occur, close proximity or contact of cells is required for full induction. These results are consistent with other investigations demonstrating that conditioned medium from M and other cell types did not induce viral replication in U1 and ACH2 cells to the same magnitude as that obtained by cell-cell contact (20,27). The inductive effect required the presence of viable M , since we found that paraformaldehyde-fixed M did not induce viral replication.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have demonstrated that coculture of latently infected cells with M and other cell types induced the nuclear localization of NF-B (20,(25)(26)(27)(28). To determine the kinetics of the activation of NF-B by coculture, nuclear proteins were isolated from cocultures of U1 or ACH2 and M at 0, 3, 6, and 24 h, and the amounts of NF-B p50 and p65 in the nuclear extracts were determined by ELISA.…”
Section: Induction Of Nf-bmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, establishment of HIV-1 infection and induction of proviral expression in monocytes/macrophages require endogenous C/EBP factors (27,28). Although NF-B has been shown to be involved in endothelial cell-induced activation of HIV-1 transcription in infected cells (20,52), the role of C/EBP␤ in macrophageendothelial cell interactions is not known.…”
mentioning
confidence: 99%
“…One potential mechanism by which endothelial cells create a microenvironment that is favorable for HIV-1 replication is by inducing transcription factors such as NF-B or C/EBP␤ in macrophages through either direct cell contact or soluble factors (20). In this study, we specifically address the role of C/EBP␤ in the regulation of HIV-1 expression in response to endothelial cell-derived signals.…”
mentioning
confidence: 99%